T Tauri stars as γ-ray source in the Rho Ophiuchi region - Filócomo, Agostina (2020)
More than 30% of γ -ray sources detected in the last source catalog of the Fermi satellite have no observational counterpart at other frequencies. A significant fraction of these sources is positionally in agreement with star-forming regions dominated by associations of T Tauri stars. Rho Ophiuchi, which is one of the closest star-forming regions, matches the unidentified Fermi source 4FGL J1625.3-2338. In this work we modeled the spectral energy distribution considering some dominant radiative processes in T Tauri stars. Accounting for a total of 22 Class III T Tauri stars in the region, integrated γ -ray luminosity in the 100~MeV to 100~GeV energy range is consistent with the observed in the catalog for the 4FGL J1625.3-2338 source.